Mild traumatic brain injury-induced persistent blood–brain barrier disruption is prevented by cyclosporine A treatment in hypertension - Lendvai-Emmert, Dominika; Magyar-Sumegi, Zsofia Dina; Hegedus, Emoke; Szarka, Nikolett; Fazekas, Balint; Amrein, Krisztina; Czeiter, Endre; Buki, Andras; Ungvari, Zoltan; Toth, Peter (Frontiers in Neurology, 2023)
Introduction Mild traumatic brain injury (mTBI) and hypertension synergize to induce persistent disruption of the blood–brain barrier (BBB), neuroinflammation and cognitive decline. However, the underlying mechanisms are not known. Cerebral production of Cyclophilin A (CyPA) is induced in hypertension and after TBI, and it was demonstrated to activate the nuclear factor-κB (NF-kB)- matrix-metalloproteinase-9 (MMP-9) pathway in cerebral vessels leading to BBB disruption. Methods To test the role of CyPA in mTBI- and hypertension-induced BBB disruption we induced mTBI in normotensive and spontaneously hypertensive rats (SHR), then the animals were treated with cyclosporine A (a specific inhibitor of CyPA production) or vehicle for 7 days. We assessed BBB permeability and integrity, cerebral expression and activity of the CyPA-NF-kB-MMP-9 pathway, extravasation of fibrin and neuroinflammation. Results We found that mild TBI induced BBB disruption and upregulation of the CyPA-NF-kB-MMP-9 pathway in hypertension, which were prevented by blocking CyPA. Cyclosporine treatment and preservation of BBB function prevented accumulation of blood-derived fibrin in the brain parenchyma of hypertensive rats after mTBI and reversed increased neuroinflammation. Discussion We propose that mTBI and hypertension interact to promote BBB disruption via the CyPA-NF-kB-MMP-9 pathway, and inhibition of cyclophilin production after mTBI may exert neuroprotection and improve cognitive function in hypertensive patients.